Faktor Risiko Depresi Antenatal Di Puskesmas Jagir Dan Tanah Kali Kedinding Surabaya - Hasanah, Zumroh; Joewono, Hermanto Tri; Muhdi, Nalini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: To find out the prevalence and analyze the risk factors (biological, psychological and social) of pregnant women who experience antenatal depression at health center of Jagir and Tanah Kali Kedinding Surabaya.Methods: A cross sectional study design, after got the ethical clearance certificate, the subjects were pregnant women who visited antenatal clinic and meet the criteria in Mei-Juni 2019. Independent variables were biological factors : a history of Premenstrual dysphoric disorder (PMDD), and obstetric status (age, history of miscarriage and mode of delivery, and risk of pregnancy), psychological factors : the history of child abuse and negative life events and social factors : marital conflict, pregnancy status, family/spouse/social support, and financial stress. The dependent variable was determined by Edinburgh Postnatal Depression Scale (EPDS) with a cut off value of 10. Statistics analysis used accordingly.Results: The prevalence of antenatal depression was 18.95%. The statistic calculation found that age (P=0.168), Â history of miscarriage and mode of delivery (P=0.540), risk of pregnancy (P=0.756), history of PMDD (P=1.000), history of child abuse (P=0,219), negative life events (P=0.870), marital conflict (P=1,000), pregnancy status (P=1,000), family, spouse and social support (P= -), and financial stress (P=1,000).Conclusion:There was no relationship between antenatal depression and the age of pregnant women, history of miscarriage and mode of delivery, pregnancy risk, history of PMDD, history of child abuse, negative life events, marital conflict, pregnancy status, family, spouse and social support, and financial stress.